Women’s impressions of their inpatient birth care as provided by family physicians in the Shizuoka Family Medicine Training Program in Japan - Yokota, Mariko (BioMed Central, 2013)
BACKGROUND: Even though Japan faces serious challenges in women’s health care such as a rapidly aging population, attrition of obstetrical providers, and a harsh legal climate, few family medicine residency training programs in Japan include training in obstetrics, and the literature lacks research on women’s views of intra-partum pregnancy care by family physicians. FINDINGS: In this exploratory study, we conducted semi-structured qualitative interviews with five women who received their admission, intrapartum, delivery and discharge care from family medicine residents in the obstetrics ward of a community training hospital. Four women had vaginal births, and one had a Cesarean section. Three were primiparous, and two multiparous. Their ages ranged from 22–33. They found value in family physician medical knowledge and easy communication style, though despite explanation, some had trouble understanding the family physician’s scope of work. These women identified negative aspects of the hospital environment, and wanted more anticipatory guidance about what to expect physically after birth, but were enthusiastic about seeing a family doctor after discharge. CONCLUSIONS: These results demonstrate the feasibility of family medicine residents providing inpatient birth care in a community hospital, and that patients are receptive to family physicians providing that care as well after discharge. Women’s primary concerns relate mostly to hospital environment issues, and better understanding the care family physicians provide. This illustrates-areas for family physicians to work for improvements.